Model Susceptible-Infected-Recovered (SIR) Dampak Penerapan PSBB Terhadap Kasus Covid-19 Di Pekanbaru - Soleh, Mohammad Soleh; Melvy Utari Permadhi; Wartono; Irma Suryani; Elfira Safitri; Riry Sriningsih (Pendidikan Matematika Universitas PGRI Yogyakarta, 2024)
Covid-19 has become a global pandemic in the 21st century. Various efforts to control its spread have been made. Isolation or regional quarantine is one of the efforts made by almost all countries in the world. Indonesia modified the lockdown by implementing 'Large-Scale Social Restrictions (PSBB)'. Before and during the implementation of PSBB, there have been many pros and cons in the community. By using the SIR model and Euler method, the impact before and after the implementation of PSBB in Pekanbaru city is compared. Based on daily data of Covid-19 cases in Pekanbaru city, it is obtained that the value of the basic reproduction number before and after the implementation of PSBB are and respectivel. This condition confirms that either without or by implementing PSBB, Pekanbaru city will be free from Covid-19. Simulation of Covid-19 cases before and after PSBB graphically also shows a situation that will be free from disease. However, without implementing PSBB, the number of infected will jump drastically after some time even though it will eventually decrease, while by implementing PSBB there is no spike. Thus, the implementation of PSBB can be an alternative to control Covid-19. Keywords: Basic reproduction number, Covid-19, PSBB, SIR model, Euler methods.